Case Study: Decolonising the Curriculum – An Exemplification. Issue 1 (11th January 2022) - Wilson, Caroline; Broughan, Christine; Daly, Guy
Abstract : Coventry University has made a strategic commitment to address the dimension of 'race' in its learning and teaching. Central to this is the establishment of a cross-institution curriculum change initiative called 'Curriculum 2025'. The case study shared here details how we are approaching this task and some early reflections. Two things are explained: first, the provision of resources for staff who want to learn more about possible actions to take; second, our approach to working alongside course teams on new materials, often designed as reusable learning objects. An example of such a learning object is discussed which uses Wikipedia to enable students from diverse backgrounds to examine critically academic texts, books and other resources to understand how their learning may be skewed in favour of Western-originated thought and to identify alternative perspectives. The student activity also provides a co-creation opportunity, in that students are discovering the curriculum for themselves.